A graph-cut based algorithm for approximate MRF optimization - Shabou, A.; Tupin, F.; Darbon, J. (2009 16th IEEE International Conference on Image Processing (ICIP), 2009)
This paper copes with the approximate minimization of Markovian energy with pairwise interactions. We extend previous approaches that rely on graph-cuts and move making techniques. For this purpose, a new move is introduced that permits us to perform better approximate optimizations. Some experiments show that very good local minima are obtained while keeping the memory usage low.